Human Rights: From Poetry to Financial Reports, A Prediction on how the Environmental, Social, and Governance World can Change Everything - Victor Cabezas Alban (Latin American Law Review)
This paper argues that the progressive inclusion of human rights criteria in ESG indicators can have an unprecedented impact. Based on a conceptual study of the ESG legal framework and major normative developments in Europe, this paper presents indicative evidence of a new set of incentives and obligations for transnational corporations. The novelties that the ESG movement brings could be extremely useful in advancing the agenda of international human rights law which, for years, has suffered the ravages of having no real enforcement mechanisms at the international level. In Europe, for example, human rights due diligence could soon condition permits in the world of mergers and acquisitions, and the list of potential impacts is long. Based on a systematization of regulatory developments and some projections, this research shows the emergence of a new and potentially transformative relationship between human rights and the financial sustainability of private companies.